Disability: a model and measurement technique. Issue 2 (June 1976) - Williams, R G; Johnston, M; Willis, L A; Bennett, A E
Abstract : Current methods of ranking or scoring disability tend to be arbitrary. A new method is put forward on the hypothesis that disability progresses in regular, cumulative patterns. A model of disability is defined and tested with the use of Guttman scale analysis. Its validity is indicated on data from a survey in the community and from postsurgical patients, and some factors involved in scale variation are identified. The model provides a simple measurement technique and has implications for the assessment of individual disadvantage, for the prediction of progress in recovery or deterioration, and for evaluation of the outcome of treatment regimes.